Leveraging microbiome-based interventions to improve the management of neurodegenerative diseases: evidence for effects along the microbiota-gut-brain axis - Auclair-Ouellet, Noémie; Kassem, Ola; Bronner, Stéphane; Oula, Marie-Laure; Binda, Sylvie (Frontiers in Nutrition, 2025)
The microbiota-gut-brain axis (MGBA) has recently emerged as a useful model for the understanding of the onset and progression of neurodegenerative diseases (NDDs). Microbiome-based interventions using biotic supplements (probiotics, prebiotics, synbiotics, postbiotics) can modulate the MGBA and constitute relevant solutions to help reduce the risk of neurological changes associated with NDDs and manage symptoms. This narrative review provides a summary of the functioning of the MGBA and of its interactions with disease processes involved in the onset and progression of NDDs. Microbiome-based interventions and their mechanisms of action are reviewed, and important considerations for the design of interventions are discussed. Next, preclinical and clinical studies on the potential of microbiome-based interventions in Alzheimer’s disease (AD), Parkinson’s disease (PD), Multiple Sclerosis (MS), Amyotrophic Lateral Sclerosis (ALS), and Huntington’s disease (HD) are reviewed. Evidence related to biomarkers of pathology (e.g., beta-amyloid or alpha-synuclein protein depositions), neuroinflammation, and metabolic activity is summarized, along with emerging evidence for the improvement of clinical symptoms and disease trajectories. Overall, preclinical studies show that microbiome-based supplements have significant positive effects on mechanisms and pathways involved in the pathophysiology of NDDs. Clinical studies show that these interventions provide important benefits both in terms of biomarkers and clinical symptoms. However, evidence is limited in some key clinical areas, such as mental wellbeing in AD and cognition in PD, and for the management of clinical symptoms in ALS and HD overall. Gaps in knowledge and open questions as well as perspectives for future research are discussed.